Kinetic sorption of Cr(VI) into solvent impregnated porous microspheres - Illanes, Cristian Omar (2008)
The sorption rates of Cr(VI) ion from acid chromate solutions with Aliquat 336 impregnated microspheres (MS) were examined. MS of polysulfone (PSf) and poly(styrene-acrylenitrile) (SAN) were prepared by phase inversion process. The MS obtained have different size and morphology. The sorption behavior and the rate-controlling sorption step have been discussed from the Elovich equation, pseudo-second order and Crank kinetic models. Even all models gave satisfactory correlations with the experimental data, the Crank model showed to be more realistic and appropriate to interpret the Cr(VI) kinetic sorption results. These analysis indicate that the intraparticle solute diffusion is the rate-controlling sorption step, and suggest that there is a surface diffusion contribution to the overall Cr(VI) mass transport inside the MS which is more important as the MS pore size decreases.